The Impact of Socio-Emotional Intelligence Training on Teacher's Performance - Ali Turi, Jamshid; Muhammad Faizal, A. Ghani; Sorooshian, Shahryar; Abbas, Qaiser (GLOBE Research Journal, 2017)
Researchers and practitioners suggest acquisition of socio-emotional intelligence skills and competencies for the teacher in the age of stresses, individualism, and materialisms; to improve teacher’s effectiveness and performance and to raise a socially and emotionally intelligent child. The study contains an investigation of the impact of socio-emotional intelligence training on teacher performance and productivity. Results indicate that socio-emotional intelligence has a positive correlation with teacher performance. Results show positive impacts of Socio-emotional intelligence training on teachers’ performance and productivity. Data were analyzed for gender and qualification variable using SPSS, Cronbach Alpha was calculated, and descriptive statistics were used for data analysis. Researchers and practitioners suggest acquisition of socio-emotional intelligence skills and competencies for the teacher in the age of stresses, individualism, and materialisms; to improve teacher’s effectiveness and performance and to raise a socially and emotionally intelligent child. The study contains an investigation of the impact of socio-emotional intelligence training on teacher performance and productivity. Results indicate that socio-emotional intelligence has a positive correlation with teacher performance. Results show positive impacts of Socio-emotional intelligence training on teachers’ performance and productivity. Data were analyzed for gender and qualification variable using SPSS, Cronbach Alpha was calculated, and descriptive statistics were used for data analysis.